Effect of Cu-ZnO nanoparticles on the photocatalytic degradation of reactive red 120 - S, David Jereil; S M, Shankar; K, Sudhakar; Arumugam, Ganeshkumar [UNESP]; Annamalai, Padmanaban; Dhanalakshmi, Radhalayam; T．V．M．, Sreekanth; Alarifi, Abdullah (Elsevier, 2025)
Reactive red 120 is a hazardous textile dye that poses a significant threat to the environment and living organisms due to its recalcitrance and hazardous nature. This study explores the photocatalytic degradation performance of RR120 of copper-zinc oxide (Cu-ZnO) nanoparticles, synthesized using the ultrasound-assisted coprecipitation method. The physicochemical properties of the prepared nanoparticles were investigated using various analytical techniques. Cu-ZnO exhibits a hexagonal wurtzite structure of ZnO along with a minor monoclinic CuO structure. FESEM images of Cu-ZnO showed that hexagonal ZnO nanobolts and nanorods, which are due to Cu incorporation, promote crystal growth, improve optical absorption in the visible region, and increase the separation of photogenerated carriers. The band gap energy of 5% Cu-ZnO was estimated to be 2.86 eV, which is less than that of ZnO (3.17 eV). 5% Cu-ZnO demonstrates an enhanced photocatalytic degradation of RR120, achieving more than 99% with a kinetic rate of 0.013 min-1. Reusability studies confirm that 5% Cu-ZnO is stable with similar performance over multiple cycles. The increased photocatalytic activity of 5% Cu-ZnO is attributed to the introduction of Cu, which act as electron traps, suppress charge recombination, and extend the lifetime of charge carriers. This study underscores the potential of Cu-ZnO as a promising photocatalyst for RR120 degradation, offering an efficient and sustainable approach to the treatment of dye wastewater.
Keywords: Cu-ZnO nanoparticles; Photocatalysis; Reactive red 120; Recyclability; Visible light